Contribution of Renewable Energy Technologies (RETs) in Climate Resilient Approach and SDG 7 - Khanal, Ram Chandra; Shakya, Shree Raj; Bajracharya, Tri Ratna (Journal of the Institute of Engineering, 2020)
Renewable energy can contribute to adaptation to climate change, mitigation and development and may play an important role in resilient development ambition of Nepal. It has been emphasized in Nepal's Nationally Determined Contribution (NDC) and climate change policy but its potential impact on SDGs era has not been fully explored and implemented. The study used employed energy system modelling by using optimization software, reviewed literature and interacted with various experts. It has been found that renewable energy technologies (RETs) provide socio-economic and environmental benefits to people that contribute to adopting and ensuring a better adaptation to climate change based on the local context. They contribute to adaptation processes by contributing to reducing the vulnerability of people, improving adaptive capacity, and minimizing climate change risk in line with SDG 7. But these are not without challenges either. Financial, technical, institutional, policy and legal issues are major challenges to promote RETs. This study shows that theoretically altogether 4.45 million tons of CO2e of the GHG emission can be mitigated per year if all the remaining technical potential of deploying seven major RETs consisting of biogas, improved water mill, stand-alone micro-hydro plants, mini-grid micro-hydro plants, solar PV home systems, mud-ICS and metal-ICS were installed after 2012. Considering the average annual installation of these RETs, altogether 30.71 million tons of CO2e can be mitigated between the periods of 2013 to 2030 at an annual additional installation equal to average installation done in recent past three years. The initial technology investment required for implementing the above mentioned RETs ranges from NRs 97 to NRs 23,247 per ton of CO2e mitigation. This indicates that though a moderate level of the initial investment is required for promoting RETs, the GHG mitigation potential seems to be quite promising. There is no liberty of inaction, so RETs can be a good case for a triple win strategy to address mitigation – adaptation – development nexus for climate compatible development in Nepal.